AB0590 Evaluation of Dermal Thickness by Three Different Techniques in Systemic Sclerosis Patients. (15th July 2016) - Ruaro, B.; Sulli, A.; Paolino, S.; Pizzorni, C.; Cutolo, M.
Abstract : Background: Skin involvement is critical for sub-classification of systemic sclerosis into different subsets (1). Objectives: The aim of this study was to identify possible correlations between modified Rodnan skin score (mRSS), high frequency skin ultrasounds (US) and plicometer skin test (Plicometry) in the evaluation of dermal thickness (DT) in patients with (SSc). Methods: 63 SSc patients (mean age 63±12SD years, mean SSc duration 6±5 years) and 63 healthy subjects (mean age 65±15SD years) were enrolled. The three methods were employed in the seventeen areas of the skin usually evaluated by mRSS (face, fingers, dorsum of hands, forearms, arms, chest, abdomen, thighs, legs and feet) and the total score calculated, as previously reported (2, 3). US was performed by a 18 MHz probe (Esaote, Italy) reporting DT as millimetres, and Plicometry (Gima, Italy) adopting a 0–3 score as for mRSS assessment (4). Nailfold videocapillaroscopy (NVC) was performen in SSc patients to assess the proper pattern of microangiopathy. Results: A statistically significant positive correlation was found between the three methods to evaluate DT in the SSc patients (mRSS vs US r=0.53, p<0.0001; mRSS vs Plicometry r=0.98, p<0.0001; US vs Plicometry r=0.53, p<0.0001). In particular, US showed that all SSc patients had a statistically significant higher DT in the 17 areas when compared with control subjects (p=0.0001). DT measurements were found progressively higher in patients with "Early", "Active" and "Late" NVC pattern of microangiopathy. Conclusions: This study demonstrates a significant relationship between mRSS, US and Plicometry in dermal thickness evaluation in SSc patients. At the level of the seventeen skin areas analyzed by US, all SSc patients showed a statistically significant higher DT than controls. References: LeRoy EC et al. J Rheumatol 2001;28:1573–6. Moore TL, et al. Rheumatology 2003;42:1559–63. Sulli A, et al. Ann Rheum Dis. 2014;69:1140–3. Parodi MN, et al. Br J Rheumatol. 1997;36:244–50. Disclosure of Interest: None declared